Nu-Covid Eduboard: Edukasi Pesan Gizi Seimbang dan Protokol Kesehatan pada Siswa MDA Al-Muhajirin di Kota Medan - Putri Mulifajar; Marhabsyah Zhaki; Muhammad Iqbal Nasution; Hanny Nirwani; Mulki Nur Alin; Fiskianda Fadhilla; Fani Nurul Fathia; Nurul Fathi Qurrotul’aini; megawati simanjuntak (Institut Pertanian Bogor, 2022)
The Covid-19 virus is a virus that spread quickly either directly or indirectly. Prevention of the Covid-19 virus can be accompanied by a strong immune system, namely by improving a healthy lifestyle with balanced nutritional foods. Nutrition education stands for an effort to increase knowledge of nutrition and eating behavior which is important for elementary school children. The media which common to use is a playing board that can help students to understand and recall what has been conveyed. Based on this reason, the Medan Kota 02 KKN-T group designed a program to increase understanding of nutrition to prevent Covid-19 among elementary students in MDA Al-Muhajirin, in Kota Matsum IV Village. The activity began by filling out a pre-test to find out student's knowledge before receiving education material. After that, continued with delivering nutrition and covid materials including an explanation of the balanced nutrition cone, then continued with the health protocol material, playing the board game by attaching food stickers to the picture of the balanced nutrition cone and matching the picture with the health protocol description. In the last session, all the students were asked to filling out the post-test. The impact of this program is that students understand and apply how to maintain healthy and balanced nutrition guidelines (PGS) and comply with prokes. The results indicated that the value of the participants from pre-test to post-test increased not too significantly, namely by 0.034, which could be caused by knowledge bias due to distraction. The distraction may be caused by the participants' unpreparedness in receiving the material, the class conditions that are not supportive, and the lack of initiative of the participants to take notes and understand the material provided. Nu-Covid eduboard may be an alternative program for increasing student knowledge about balanced nutrition guidelines and prokes in covid-19 pandemic situation.